Penerapan Novel The Da Vinci Code Pada Medan Fiction Center Dengan Pendekatan Arsitektur Simbolik - Damanik, Yola Yohana; Aldy, Pedia; Faisal, Gun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The demand for providing facilities for fictional activities is inseparable from the role of the relationship between the user and the surrounding environment. The Artists and writers in creating works need the imagination to birth the inspiration. The main factor that becomes an element in giving birth to inspiration is the state of the environment and the atmosphere. The relationship between the nuances experienced by individuals will create certain emotions that can stimulate thinking in pervading the atmosphere so that they experience the urge to create works related to the atmosphere. Therefore, one of the largest metropolitan cities in Indonesia, Medan, needs to establish facilities in the form of Fiction Centers as a place for development and study centers, as well as appreciation aimed at supporting education, information, recreation, commercial, and appreciation of fiction. The application of The Da Vinci Code in design is expected to be a manifestation of the application of fiction into the built environment that produces architectural designs that can act as a medium of visual communication between the user and his environment so as to build emotional connections between users, functions, and buildings in order to turn on the sides of the imagination which is inspiring in giving birth to works of fiction. The research methods used include observation, documentation and secondary data in the form of case studies and comparative studies. The concept applied to the design object is "Code Inside Architecture" which is then influenced by the novel elements of The Da Vinci Code in its application and this concept also serves as a connecting point for the placement of each function. The results of this study are designing architectural objects that can arouse feelings and imagination and convey the message expected by the designer to the public through symbolic architectural principles. Keywords: Fiction Center, The Da Vinci Code, Symbolism.